The Dimension of Sufi on the Kiai Sholeh Darat Tahara (Cleanliness) Ritual and Its Implication to Moderation in Islam - Hakim, Taufiq (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This paper explains the sufistic dimension in rituals of purity well known as Tahara, namely when performing ablution and taking a Junub Washed. Kiai Sholeh Darat's pegon reading is titled Lathaif at-Thoroh wa Asrari al-Shalat. The book was written at the end of the 19th century. Through careful reading, translation of weaknesses, discussing the context of the text, and actualizing it with current conditions, an understanding of Sufistic explanations that integrates fiqh and Sufism in da'wah for the sake of an endeavor and a way of understanding a friendly and moderate Islam for Javanese society. Such patterns should be preserved so that Islam continues to be a religion of love and foster a moderate understanding of Islam for the community.